1991
DOI: 10.1002/jbmr.5650061111
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of gamma carboxylation of circulating osteocalcin (bone gla protein) in elderly women

Abstract: Osteocalcin, also called bone gla protein, is a unique noncollagenous protein of the extracellular matrix of bone that circulates in blood. Oseteocalcin contains three residues of the vitamin K-dependent gamma-carboxyglutamic acid (gla) responsible for the affinity of osteocalcin for bone mineral. In animals treated with the vitamin K antagonist warfarin, the osteocalcin content of bone is markedly reduced and the fraction of osteocalcin released into the circulation is increased. Most studies have shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(47 citation statements)
references
References 27 publications
4
42
1
Order By: Relevance
“…The increase in serum iOC in women over the age of 50 in our study is consistent with the literature [7,18,22,25,26] . However, we did not find distinct differences in ucOC when comparing pre-and postmenopausal women as observed in other studies [7,20,27,28] .…”
Section: Discussioncontrasting
confidence: 68%
“…The increase in serum iOC in women over the age of 50 in our study is consistent with the literature [7,18,22,25,26] . However, we did not find distinct differences in ucOC when comparing pre-and postmenopausal women as observed in other studies [7,20,27,28] .…”
Section: Discussioncontrasting
confidence: 68%
“…Since a part of the OC enters the bloodstream, the serum OC concentration is used as a marker of bone forma-tion (16,17 (18)(19)(20)(21) and that a high serum concentration of ucOC is related to the risk of fracture in elderly women or osteoporotic patients (22)(23)(24)(25)(26) Another striking finding in this study is that serum concentrations of OC and ucOC follow a very similar time course (27). The precise turnover of OC and ucOC in human serum has not been reported in the literature, although a study in rat models reported that one-half of the administered bone Gla protein may be cleared from serum in less than 5 minutes (17).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the three g carboxyglutamic acid residues is critical for the structure and function of OC in the fully carboxylated state allowing the binding of OC to hydroxyapatite (HA) with a high affinity, regulating the maturation of bone mineral (Hauschka & Wians 1989. However, OC also exists in the general circulation in fully carboxylated, partially carboxylated and completely uncarboxylated forms (Plantalech et al 1991, Cairns & Price 1994, Vergnaud et al 1997, Schilling et al 2005, Ferron et al 2010a. On the basis of results from human and rodent studies, serum OC concentrations have been correlated with bone formation and osteoblast number, thus being used as a serum marker of bone formation (Brown et al 1984;reviewed in Gundberg et al (2012)).…”
Section: Osteocalcinmentioning
confidence: 99%